The utility of recombinant factor VIIa as a last resort in trauma - Mamtani, Rishi (BioMed Central, 2012)
INTRODUCTION: The use of recombinant factor VII (rFVIIa) as a last resort for the management of coagulopathy when there is severe metabolic acidosis during large bleedings in trauma might be deemed inappropriate. The objective of this study was to identify critical degrees of acidosis and associated factors at which rFVIIa might be considered of no utility. METHODS: All massively transfused (≥ 8 units of red blood cells within 12 hours) trauma patients from Jan 2000 to Nov 2006. Demographic, baseline physiologic and rFVIIa dosage data were collected. Rate of red blood cell transfusion in the first 6 hours of hospitalization (RBC/hr) was calculated and used as a surrogate for bleeding. Last resort use of rFVIIa was defined by a pH≤ 7.02 based on ROC analysis for survival. In-hospital mortality was analyzed in last resort and non-last resort groups. Univariate analysis was performed to assess for differences between groups and identify factors associates with no utility of rFVIIa. RESULTS: 71 patients who received rFVIIa were analyzed. The pH> 7.02 had 100% sensitivity for the identification of potential survivors. All 11 coagulopathic, severely acidotic (pH ≤ 7.02) patients with high rates of bleeding (4RBC/hr) died despite administration of rFVIIa. The financial cost of administering rFVIIa as a last resort to these 11 severely acidotic and coagulophatic cases was $75,162 (CA). CONCLUSIONS: Our study found no utility of rFVIIa in treating severely acidotic, coagulopathic trauma patients with high rates of bleeding; and thus restrictions should be set on its usage in these circumstances.